Prevalence of Gestational Diabetes Mellitus in Pregnant Women Attending a Tertiary Care Center in Kathmandu, Nepal - Maharjan, R; Mall, D (Journal of Diabetes and Endocrinology Association of Nepal, 2025)
Gestational diabetes mellitus (GDM) is one of the most common metabolic disorders in pregnancy. Early identification and treatment are crucial to prevent adverse maternal and neonatal outcomes. This study aimed to assess the prevalence of GDM among pregnant women visiting Civil Service Hospital, Kathmandu, Nepal, between January 2023 and January 2024. Methods: Pregnant women at 26 weeks of gestation or earlier, as per clinical indication, underwent glucose challenge tests (GCT) followed by oral glucose tolerance tests (OGTT) if GCT ≥140 mg/dL. Diagnostic criteria followed the DIPSI and IADPSG recommendations. Results: Among 2108 pregnant women screened, 367 had abnormal GCT results. Of these, 140 were diagnosed with GDM. The youngest and oldest GDM cases were aged 24 and 47, respectively. Among the GDM cases, 51 were primigravida and 89multiparous. A past history of GDM was noted in 43 cases, and 83 reported a family history of diabetes mellitus. Only 409 women had awareness about GDM. Conclusion: The prevalence of GDM in this population was 6.64%. The findings underscore the importance of universal screening, especially in settings like Nepal where diabetes literacy remains low. Lifestyle modifications remain the cornerstone of treatment, with metformin and insulin as adjuncts where necessary.